Experimental Study on Sonic Vibration Grouting in Fine Silty Sand Layer - Yu Wang; Bairu Xia; Zhiqiao Wang; Shouceng Deng (Advances in Civil Engineering)
Fine silty sand layer is one of the common weak strata. It is easy to deform suddenly and induce accidents under the external load due to its loose structure and poor self-stability. To improve the stability of the strata in engineering construction, the grouting is usually used for antiseepage reinforcement in the fine silty sand layer. This paper presents the basic principle of the sonic vibration grouting, develops the experimental device and the simulated stratum condition, mixes the acidic water glass for engineering application, and carries out the experimental study on the sonic vibration grouting. The results show that the effect of the exciting force on the sonic vibration grouting is not obvious, and the vibration duration has a greater influence on it. With the increase of the vibration duration, the grouting diffusion distance is enlarging gradually and stabilizes eventually at a certain value. The vibration frequency has the greatest impact on the grouting. The grouting effect is the best when the vibration frequency is close to the natural frequency of the fine silty sand. The grouting diffusion distance is getting smaller, which means the grouting effect is becoming worse, when the vibration frequency is far away from the natural frequency of the stratum. The grouting effect in the fine silty sand layer can be improved effectively by vibration technology using the sonic vibration grouting which has excellent effect in engineering application. This paper lays a foundation for the further study on mechanism and engineering application of the sonic vibration grouting.